Oral Health Status in Diabetic and Non-Diabetic Patients on Maintenance Hemodialysis Treatment - Emilija Rambabova; Gjorgjievska, Gordana; Vasiliki Krecova; Pushevski, Vladimir; Shterjova Markovska, Zhaklina; Sefedin Biljali; Trajcheska, Lada; Oliver Bushljetikj; Aleksandar Trifunovski; Mile Carcev; Popovska, Mirjana (Balkan Cities Association of Nephrology, Dialysis, Transplantation and Artificial Organs, 2022)
Introduction. Uremic toxins and inflammation influence the oral health in patients on maintenance hemodialysis treatment. The presence of diabetes additionally aggravates the oral status. The aim of the study was to compare the oral health status in diabetic and non-diabetic patients on chronic hemodialysis program. Methods. Observational, cross-section, monocentric study was conducted in 72 hemodialysis (HD) patients divided into two groups regarding the presence of Diabetes mellitus (DM). Demographic characteristics as patients age, dialysis vintage, laboratory inflammatory markers as C-reactive protein (CRP), albumin and Interleukin 6 (IL-6) were measured at the start of the study. Also, uremic small and middle molecules as blood urea nitrogen (BUN), creatinine, β2-microglobilin (β2M), myoglobin, albumin, free light chains kappa (FLC-k), and free light chains lambda (FLC-λ) were analyzed. Patients were examined by a dentist specialist scoring the oral hygiene index (OHI) by Greene Vermillion as good, fair and poor. Presence of hyperkeratosis, periodontal disease, erosions, ulceration, erythema, pigmentations, tongue coating and uremic fetor were notified. Gingival hyperplasia (GH) was scored (1-3) with 3 for the worst score. Data was presented as mean and standard deviation for continuous and percentages for nominal values. X squared Fisher exact and Mann Whitney test were used for statistical analysis. P<0.05 was considered as significant. Results. The patients from group 1-with DM (N=26) didn’t differ from the non-diabetic group (N=46) in respect of gender, age but had significantly shorter dialysis vintage (48.68±37.45 vs. 88.13±63.29, p=0.02, respectively). From the inflammatory markers only Il6 was significantly higher in DM patients (p=0.03). All the analyzed uremic toxins-small and middle molecules also didn’t differ between the two groups. Diabetic patients were at 3 fold risk for manifestation of fissure, 4 fold risk for pigmentations and 7 fold risk for erythema (OR 3.58; CI:1.017-12.380, p= 0.003; OR 4.12; CI:0.684-22.870; p=0.02, OR 4.84; CI:1.343-17.498, p=0.000), (OR 7.25; CI:1.123-46.880, p=0.000), respectively. GH was more likely to be present in diabetic patients (35%, 54%, 11% vs 83%, 15, 0%, p=0.000, respectively). The presence of hyperkeratosis, periodontal disease, erosions, didn’t differ between the groups. Patients with DM were found with higher percentage of bad oral hygiene index (38% vs 20%), but the overall comparison of OHI showed no significant difference. Conclusion. Oral health is significantly deteriorated in dialysis patients, especially in those with inflammation. Diabetic patients are at higher risk of developing changes in the oral health status.
Keywords: hemodialysis; oral health; diabetes